Novel Glutamatergic Modulators for the Treatment of Mood Disorders: Current Status - Henter, Ioline D.; Park, Lawrence T.; Zarate, Carlos A. (CNS drugs, 2021)
The efficacy of standard antidepressants is limited for many patients with mood disorders such as major depressive disorder (MDD) and bipolar depression, underscoring the urgent need to develop novel therapeutics. Both clinical and preclinical studies have implicated glutamatergic system dysfunction in the pathophysiology of mood disorders. In particular, rapid reductions in depressive symptoms have been observed in response to subanesthetic doses of the glutamatergic modulator racemic ( R,S )-ketamine in individuals with mood disorders. These results have prompted investigation into other glutamatergic modulators for depression, both as monotherapy and adjunctively. Several glutamate receptor-modulating agents have been tested in proof-of-concept studies for mood disorders. This manuscript gives a brief overview of the glutamate system and its relevance to rapid antidepressant response and discusses the existing clinical evidence for glutamate receptor-modulating agents, including (1) broad glutamatergic modulators (( R,S )-ketamine, esketamine, ( R )-ketamine, (2 R ,6 R )-hydroxynorketamine [HNK], dextromethorphan, Nuedexta [a combination of dextromethorphan and quinidine], deudextromethorphan [AVP-786], axsome [AXS-05], dextromethadone [REL-1017], nitrous oxide, AZD6765, CLE100, AGN-241751); (2) glycine site modulators ( d -cycloserine [DCS], NRX-101, rapastinel [GLYX-13], apimostinel [NRX-1074], sarcosine, 4-chlorokynurenine [4-Cl-KYN/AV-101]); (3) subunit (NR2B)-specific N -methyl- d -aspartate (NMDA) receptor antagonists (eliprodil [EVT-101], traxoprodil [CP-101,606], rislenemdaz [MK-0657/CERC-301]); (4) metabotropic glutamate receptor (mGluR) modulators (basimglurant, AZD2066, RG1578, TS-161); and (5) mammalian target of rapamycin complex 1 (mTORC1) activators (NV-5138). Many of these agents are still in the preliminary stages of development. Furthermore, to date, most have demonstrated relatively modest effects compared with ( R,S )-ketamine and esketamine, though some have shown more favorable characteristics. Of these novel agents, the most promising, and the ones for which the most evidence exists, appear to be those targeting ionotropic glutamate receptors.